Animal breeding in sub-Saharan Africa: Toward an integrated program for improving productivity - Trail, J.C.M.; Gregory, K.E. (1984)
Describes the main ecological zones of Africa and mentions the importance of cattle in each zone, the production systems involved and the general types of cattle that can be maintained. Determines the value of previous breed productivity research in assessing current decision making.